OMNICHANNEL STRATEGY IN IMPROVING CUSTOMER EXPERIENCE IN THE DIGITAL ERA (CASE STUDY ON SYARAH BAKERY BENGKULU CUSTOMERS) - Edo Dwi Anggara; Andi Azhar (Suluh Adiluhung Publisher (SAPub), 2025)
This study aims to analyze the impact of implementing an omnichannel strategy in enhancing customer experience at Syarah Bakery, an SME in Bengkulu. Given the intense competition in the local bakery industry, this research focuses on how the integration of online and offline channels can create a consistent and satisfying experience for customers. The approach used in this study is quantitative with a case study design, where data was collected through questionnaires and interviews with customers and the manager of Syarah Bakery. The study sample consisted of 350 respondents who had used various service channels. The results of the analysis using the Partial Least Squares (PLS) method indicate that service consistency, channel integration, service personalization, ease of access, and responsiveness significantly influence customer experience, with an R² value of 0.68. These findings highlight the importance of service consistency and channel integration in creating seamless customer experience. The study also provides recommendations for Syarah Bakery to improve their omnichannel strategy through service personalization, ease of access, and responsiveness to enhance customer satisfaction and loyalty in the digital era.